La discapacidad como forma de diversidad humana en la narrativa española actual. El significado de las imágenes de la discapacidad en Lectura fácil de Cristina Morales - Ziarkowska, Justyna (Studia Romanica Posnaniensia, 2020)
The representation of the disability in the recent Spanish narrative raises several questions: by the role and place that the excluded occupy in the fictitious worlds, by the point of view and the tonality in which they are represented, by the reaction of the other participants of fiction. In the recent novel by Cristina Morales titled “Lectura fácil”, four protagonists are presented with intellectual disability. For his condition the metaphor of slavery is used, but it is not an internal oppression, but external and institutional one. The social system is much more oppressive and violent than the experience of the disease itself. They radicalize and oppose the therapeutic and normalizing attempts of society and thus question the dominant culture. The presentation of the disability made by Morales lacks the perspective of superiority, but also cedes from a different emotional perspective compared to the portraits of normative characters.